Problems Faced by English Teacher Candidates in Developing Test Kits for Assessing Students’ Learning - Ari Purnawan; Asfar Arif Nurharjanto; Annisa Nurul Ilmi (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2023)
Background: Learning assessment has been left behind compared to other components of teaching such as instructional methods or media development. This paper aims to describe problems faced by English teacher candidates studying at the English Education Department of a university in Java, Indonesia in developing test kits for assessing students’ learningMethodology: This study is qualitative in nature. The investigation involved 28 teacher candidates taking two sequential courses on testing namely English Learning Assessment and English Language Learning Test Development who were then asked to write a set of English learning achievement tests as their end-of-class mini project. A total of 1052 multiple choice questions were analyzed by three investigators to reveal the teacher candidates’ problems in developing test kits. Problems are reported and described quantitatively. Findings: The study reveals that the students face difficulties in formulating test kit formats, stems, options, and texts.Conclusion: Recommendations include education for writing test questions and improving or revising the learning syllabus and materials of the above-mentioned courses on language learning assessment Originality: The number of questions or participants can be improved as well as the scope of analysis to make the study more reliable.